1992
DOI: 10.1021/bi00152a010
|View full text |Cite
|
Sign up to set email alerts
|

Functional signal peptide reduces bilayer thickness of phosphatidylcholine liposomes

Abstract: To investigate the interaction between a signal peptide and the lipid bilayer, two kinds of peptides, L8-M5 (L8 = MRL8PLAALG, M5 = KVFER) and L14-M5 (L14 = MRL14PLAALG), were examined in membranes composed of dioleoylphosphatidylcholine (DOPC). Peptides L8 and L14 are artificially designed signal sequences, and M5 is the N-terminal five residues of human lysozyme; L8 mediated effective secretion of human lysozyme in yeast, while L14 did not [Yamamoto, Y., et al. (1987) Biochem. Biophys. Res. Commun. 149, 431-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…The R 0 value for the tryptophan-Py-3-Py donor-acceptor pair was 26.9 Å, which was comparable to the values for tryptophan-pyrene pair (Dobretsov et al, 1982;Tahara et al, 1992). In the calculation of R 0 , the value of k 2 was 2/3, and that of the (Schroeder et al, 1988;Sweet et al, 1987).…”
Section: Effects Of E2 On the Bulk And The Annular Lateral Diffusion supporting
confidence: 60%
“…The R 0 value for the tryptophan-Py-3-Py donor-acceptor pair was 26.9 Å, which was comparable to the values for tryptophan-pyrene pair (Dobretsov et al, 1982;Tahara et al, 1992). In the calculation of R 0 , the value of k 2 was 2/3, and that of the (Schroeder et al, 1988;Sweet et al, 1987).…”
Section: Effects Of E2 On the Bulk And The Annular Lateral Diffusion supporting
confidence: 60%
“…Pyrene was then excited 1 min later through energy transfer from tryptophan (excitation ϭ 286 nm), and fluorescence emission spectra of pyrene were recorded. Considering that the Forster radius (the energy transfer-limiting distance) for the tryptophan-pyrene donor-acceptor pair is 3 nm (27), only pyrene located in the annular lipid (adjacent to proteins) was excited, and the fluidity of the annular lipid was considered proportional to the ratio F e /F m , where F e and F m are the fluorescence intensities of pyrene eximer (emission ϭ 480 nm) and monomer (emission ϭ 373 nm), respectively. Pyrene was then excited at 334 nm, and the bulk fluidity was considered to be proportional to the ratio F e /F m obtained with the 334-nm excitation wavelength.…”
Section: Chemicals-a␤mentioning
confidence: 99%
“…This finding suggests that A␤ modulates membrane function by a nonreceptor-mediated mechanism, potentially as a result of altering the physico-chemical properties of membrane constituents, including lipids and proteins (13)(14)(15)(16). Indeed, previous membrane equilibrium binding experiments have demonstrated that the A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment is highly lipophilic (K P Ͼ 10 2 ); the peptide intercalates deep into the membrane bilayer hydrocarbon core, as determined by small angle x-ray diffraction approaches (15). In addition, aggregated A␤ has strong electrostatic interactions with the surface of model membranes that appear to mediate its neurotoxicity (17).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The thickness of the hydrophobic segment of the DMPC bilayer is around 29Å (21). The spacing between the phosphorous atom in the lipid headgroup and the first C atom of the acyl chain is about 5Å (22).…”
Section: Probable Location Of the Peptide In The Bilayermentioning
confidence: 99%